A Comprehensive Review of Vehicle-to-Grid Technology Effect on Frequency Stability in Electric Power Systems - Dewi, Citra; Adrianti, Adrianti; Nasir, Muhammad (Andalasian International Journal of Applied Science, Engineering and Technology, 2025)
Vehicle-to-Grid (V2G) technology is an innovative concept designed to support frequency stability by enabling two-way energy exchange between electric vehicles (EVs) and the power grid, especially in systems with high penetration of renewable energy resources. This paper examines the battery electric vehicles’ demand nature also as an ancillary support resource to address intermittency of renewable energy sources and grid frequency support through V2G technology. The study highlights technological issues such as degradation rates of batteries, communication difficulties, and scaling problems alongside issues of regulation and market that encompass large-scale implementation of V2G. Tackling the effectiveness of V2G systems in frequency regulation The effectiveness of approaches like virtual inertia emulation, enhanced control algorithms, and decentralized frameworks are discussed as ways of enhancing V2G systems. These findings reaffirm that V2G has tremendous potential in the electric grid yet, it must be noted that solving these issues remains critical through transformational research and policy strategy. The conclusions help to better understand the prospects for improving V2G towards more accurate support for frequency stability in transition to sustainable energy systems.